Scheme To Watermark Digital Text Documents - Tinauli, Musstanser (2007)
For this thesis watermarking is defined as a combination of digital fingerprints and digital watermarking. Content-based fingerprints and other copyright information are submerged together within the document during the marking process. Multi-level security is ensured by insertion of the watermark at two distinct and independent levels within the same document. The watermark is inserted in the unformatted and the formatted text to provide the dual level of security.